Psychometric Properties of the Quick Inventory of Depressive Symptomatology-Self-Report (QIDS-SR) in Depressed Adolescents - Zhang, Wu-Yang; Zhao, Yan-Jie; Zhang, Yao; He, Fan; Pan, Hong-Qing; Cheung, Teris; Ungvari, Gabor S.; Li, Shu-Ying; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
Background: Accurate and reliable self-report measurement tools on examining depressive symptoms were scant in child psychiatry. This study assessed the psychometric properties of the Chinese Version of the Quick Inventory of Depressive Symptomatology - Self-Report (C-QIDS-SR) among depressed adolescents in China. Methods: Adolescents with major depressive episodes or bipolar depressive episodes were assessed using the C-QIDS-SR. The structure validity of the C-QIDS-SR was estimated using principal component analysis with varimax rotation. Results: A total of 246 depressed adolescents were included. Cronbach’s alpha was 0.77. Correlation coefficient between baseline and endpoint assessments was 0.49 (p<0.001), whereas, the correlation coefficient between the C-QIDS-SR and the Hamilton Rating Scale for Depression–17 items (HAMD-17) was 0.63 (p<0.001). Principal component analysis with varimax rotation demonstrated the unidimensional structure of the C-QIDS-SR. Conclusion: The C-QIDS-SR is an acceptable, reliable and valid instrument to measure depressive symptoms in adolescents.